The Essence of Lease as Economic Category (Economics and region, 2019)
Economic nature and essence of lease is elucidated in the article, socio-economic preconditions of its development are considered in the system of relations of property. Problem questions of using of such concepts as “leasing”, “employment”, “hire” at entering into contracts are investigated.
Keywords: lease; hire; leasing; concession; contract